The frequency of cerebral microbleeds increases with CHADS2 scores in stroke patients with non‐valvular atrial fibrillation. Issue 3 (11th October 2012) - Song, T.‐J.; Kim, J.; Lee, H. S.; Nam, C. M.; Nam, H. S.; Heo, J. H.; Kim, Y. D.
Abstract : Background and purpose: Cerebral microbleeds (CMBs) are extravasations of blood from lipohyalinized or amyloid angiopathic cerebral arterioles, and the presence and numbers of CMBs are significantly associated with the development of oral anticoagulation (OA)‐related intracranial haemorrhage (ICH). The aim of this study was to investigate whether there is a difference in CMBs burden according to CHADS2 scores or CHA2 DS2 ‐VASc scores in non‐valvular atrial fibrillation (NVAF) patients. Methods: We included 550 ischaemic stroke patients who had NVAF and who had undergone brain magnetic resonance imaging (MRI) with gradient‐recalled echo (GRE) T2 sequences from our prospective stroke registry between January 2005 and November 2011. We calculated CHADS2 scores and CHA2 DS2 ‐VASc scores for all patients based on their underlying cardiovascular diseases. The presence, location and number of CMBs were assessed in each patient. We also investigated whether the CMBs were actually associated with the development of ICH during follow‐up. Results: The mean patient age was 70.4 ± 10.5 years, and 324 (58.9%) patients were men. One‐hundred and seventy‐three patients (31.5%) had CMBs detected on GRE MRI. Higher CHADS2 scores or CHA2 DS2 ‐VASc scores were strongly associated with the presence and number of CMBs. During follow‐up of median 3.1 ± 1.6 years, the presence of CMBs was independently associated with the development of ICH, whilst the CHADS2 scores or CHA2 DS2 ‐VASc scores were not. Conclusions: Considering the positive association between the presence of CMBs and OA‐related ICH, our results suggest that the increase in ICH in high‐risk groups during OA may be related to an increased burden of CMBs.